2021
DOI: 10.1016/j.jcot.2021.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Higher altitude leads to increased risk of venous thromboembolism after acetabular and pelvic ring injury

Abstract: Introduction: There is a high post-operative incidence of venous thromboembolisms (VTEs), specifically deep vein thrombosis (DVT) and pulmonary embolism (PE), in pelvic ring and acetabular fractures, and identification of risk factors for VTEs is crucial to decrease this highly morbid complication. High altitudes have a known physiological effect on the body that may predispose patients to developing VTEs in the postoperative period. The purpose of this study was to investigate the relationship between pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is well known that high altitudes induce physiological changes for adaption to a relatively lower oxygen tension environment. Previous literature has shown that these changes may predispose to thrombogenesis by way of hypercoagulability and venous stasis [ 2 , 15 , 16 ]. As the oxygen tension lowers at higher altitudes there is a compensatory increased red blood cell and resulting hemoconcentration [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that high altitudes induce physiological changes for adaption to a relatively lower oxygen tension environment. Previous literature has shown that these changes may predispose to thrombogenesis by way of hypercoagulability and venous stasis [ 2 , 15 , 16 ]. As the oxygen tension lowers at higher altitudes there is a compensatory increased red blood cell and resulting hemoconcentration [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These records allow for the analysis of multiple parameters, including procedure data, location, medical comorbidities, medical prescriptions, and post-operative follow-up care. Prior orthopedic studies have used this database for clinical investigation and it is well-published in the literature [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations